Application Of Utaut2 On Peer To Peer (P2p) Lending Platform In Malaysia - Ramachandran, Lingeswary (2024)
Peer to Peer (P2P) lending has developed into an indispensable part of financial ecosystem. P2P lending platforms in Malaysia are registered with the Securities Commission of Malaysia (SCM). P2P lending platforms are relatively new in Malaysia. Despite the growth of the P2P lending sector in Malaysia, it still faces significant challenges and limitations that prevent it from achieving mainstream adoption. These challenges include modest participation rates compared to conventional lending, regulatory barriers, perceived higher risks, and trust disparity among potential investors. Additionally, issues such as information asymmetry, high default rates, and the need for better performance metrics and risk management strategies hinder the sector's development and investors’ confidence. Addressing these issues is crucial for the P2P lending industry to expand and become sustainable within Malaysia's financial ecosystem. Hence, this study aims to investigate the individual investors’ intention to invest in a P2P lending platform in Malaysia. The theoretical framework which is applied in this study is model of Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) which has been further extended by integrating an independent variable, namely Investing Experience.